CURRENT CONCEPTS IN CYSTITIS: EPIDEMIOLOGY, PATHOGENESIS, AND CONTEMPORARY MANAGEMENT - Kamoljonova Go’zaloy Odiljon qizi (TADQIQOTLAR, 2025)
Abstract. Cystitis—the inflammation of the urinary bladder—remains one of the most common bacterial infections worldwide. Acute uncomplicated cystitis is usually caused by Escherichia coli, whereas complicated and recurrent forms involve a broader range of uropathogens and host factors. Recent guideline updates emphasise rising antimicrobial resistance, the need for antibiotic-sparing strategies, and individualised prevention. This three-page review synthesises the latest evidence on epidemiology, pathophysiology, clinical presentation, diagnostic criteria, and evidence-based treatment options, drawing on the 2024 European Association of Urology (EAU) and 2024 Infectious Diseases Society of America (IDSA) recommendations. Early recognition, appropriate antimicrobial stewardship, and patient-centred preventive measures are critical to reducing morbidity and healthcare costs associated with cystitis.